(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
This study examines the impact of demonetization announcement effect on the returns of stock market & quantum of Investment through traded value in India for a very short period of time. The study examines the daily data of closing prices of S&P CNX Nifty Index and its traded value during pre and post demonetization periods. This is a new aspect that has been experimented by the existing government to eradicate black money, counter tax-evasion and destroy counterfeit currency from the Indian economy. The paper is basically concentrating on the effect of this government strategy on the capital market returns & its turnover. There is a mixed reaction on demonetization announcement among the different stakeholders of the economy. The present study is an attempt to understand the reaction of Indian capital market after demonetization. A standard event study methodology has been adopted to examine the pattern of changes that has taken place surrounding 50 days of the announcement date.